DEVELOPING MATERIAL FOR LEARNING VOCABULARY BASED ON PUZZLE GAME FOR THE STUDENTS MAJORING IN ELECTRICAL ENGINEERING OF SMK NEGERI 2 MEDAN - Nur Fitriani; Amrin Saragih; Safrida Lubis (Universitas Negeri Medan, 2018)
The objectives of this study were: (1) to develop reading material for tenth grade students of SMK Negeri 2 Medan, (2) to develop students’ vocabulary by playing puzzles as the task. This study was conducted by Research and Development (R&D). The research procedures were adapted from Borg and Gall. This research were designed through six phases; 1) gathering data and information, 2) analyzing the data, 3) designing materials, 4) validating materials, 5) revising, and 6) final product. The data of this research were taken from existing materials, syllabus, teacher’s interview and students’ questioners. The result of this study showed that the students’ existing material were not relevant to electrical engineering program. The vocabulary that students’ get from the existing materials was less. The designing material was validated by English teacher and English lecturer. The product of this study is a set of reading material entitled “electricity holic” for students in SMK Negeri 2 Medan. The reading materials consist of three genres; descriptive, narrative and recount. Key words: Reading material, Research and Development (R&D), SMK Negeri 2 Medan, Puzzle, Vocabulary.